An?lise multitemporal e espacial do uso e cobertura das terras no munic?pio de Casa Nova, Bahia, no per?odo de 1996 a 2011 - Almeida, Augusto Pontes (2013)
The action of man over nature haphazardly and without adequate planning has led to imbalances in the various terrestrial ecosystems. Thus, it is necessary to formulate strategies to facilitate the balance between human activities and the strengths and weaknesses of environmental systems. One of the strategies used today is the analysis of the use and land cover across sub-basins, an innovation of the technique. Based on that this work has as main objective to analyze changes in land use and land cover in the municipality of Villa Nova, BA, through the use of geotechnology, for the years 1996, 2003 and 2011. The study area is located in the far north of the state of Bahia, Bahia and semi-arid shores of Lake Sobradinho, between the geographical coordinates 41?53' W and 40?39' W and 8?42' S and 09?47' S. The multitemporal analysis for use and land cover featured images of LANDSAT 5 TM, belonging to the municipality for the years 1996, 2003 and 2011, and to reach the purpose were followed methodological procedures that guided this research, structured in four steps: the first step were acquired vector data (GIS database from various sources) and raster data (Landsat and ASTER MDT). The second stage consisted in pre-processing of LANDSAT scenes where applied fixes atmospheric tilt solar and geometric mosaic and clip area. The third step was the digital image processing by performing statistical analysis, preparation of colored compositions, contrast enhancement, image classification and filtering. The fourth step was the post-processing is performed fieldwork for data collection with the help of GPS, these data provided support the calculation of Kappa indices, PABAK and errors of commission and omission, validating the maps with the realization of cross-tabulation between use and land cover, the years of study, and sub-basins extracted from the digital terrain model. The results from this study showed there were changes over time, such as farming areas which decreased missing for other uses. The techniques used allowed the identification of dynamic classes use and land cover in the study region.